Processing parameters in production of pumpkin powder using forced hot- air frying in ‘bingka’ baking - Nik Murzaini, Nik Masturah (2019)
Currently, pumpkin powder is one of the main pumpkin products due to its longer shelf life and it can act as a substitute for pumpkin flesh in different types of formulated foods such as cakes, biscuits, and noodles. However, this may affect the quality of the products in terms of colour and nutritional content. Therefore, this work focused on producing pumpkin powder from different parts and evaluating the effects of powder substitution on the physical properties of ‘bingka’. Sliced pumpkin samples (peeled, unpeeled, and skin) were immersed in limewater as a pretreatment step. Then, the treated pumpkin samples were dried using an air fryer at different temperatures and times. The optimum temperature and time for the production of pumpkin powder and baked ‘bingka’ were determined using response surface methodology (RSM). Conventionally, ‘bingka’ is made from coconut milk, eggs, sugar, and butter. The selected temperatures for baking ‘bingka’ were in the range of 130–150 °C and the baking time was between 25 and 35 min. The optimum drying conditions for peeled and unpeeled samples were 80 °C and 120 min, and 90 °C and 120 min were needed to dry the pumpkin skin. The moisture contents were 5.18% for peeled pumpkin, 6.16% for unpeeled pumpkin, and 6.23% for pumpkin skin. The results for colour in terms of L* values are 64.10 (peeled pumpkin), 64.43 (unpeeled pumpkin), and 62.27 (pumpkin skin). Next, the powder obtained at the optimum conditions was used in ‘bingka’ baking. The ‘bingka’ baked using peeled pumpkin at optimum baking temperature (130 °C) and time (25 min) in the air fryer has higher moisture content (45.92%) as compared to those baked in the convection oven at higher baking temperature (180 °C) and time (60 min), with moisture content of 42.96%. The L* values of ‘bingka’ made from peeled and unpeeled pumpkin powder are 61.51 ± 0.26 and 63.10 ± 0.32, respectively, whereas the L* values of ‘bingka’ made from peeled and unpeeled pumpkin are 60.09 ± 0.57 and 63.67 ± 0.43, respectively. The overall liking shows that the ‘bingka’ made from peeled pumpkin baked by using the air fryer is preferred in terms of texture (hardness and chewiness), pumpkin flavour, appearance, and colour. It can be concluded that pumpkin powder can be used as a substitute for raw material by comprising the appearance of the product.